2008
DOI: 10.1161/circresaha.107.165936
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Cardiovascular Disease by a Dysfunctional Prostacyclin Receptor Mutation

Abstract: Abstract-Recent increased adverse cardiovascular events observed with selective cyclooxygenase-2 inhibition led to the withdrawal of rofecoxib (Vioxx) and valdecoxib (Bextra), but the mechanisms underlying these atherothrombotic events remain unclear. Prostacyclin is the major end product of cyclooxygenase-2 in vascular endothelium. Using a naturally occurring mutation in the prostacyclin receptor, we report for the first time that a deficiency in prostacyclin signaling through its G protein-coupled receptor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 33 publications
5
110
0
Order By: Relevance
“…Prostacyclin also acts as a critical cardio/cytoprotective agent during acute myocardial ischemia ( 15-17 ) and enhances endothelial cell (EC) survival, supporting neovascularization ( 18 ). Several single-nucleotide polymorphisms occur in the hIP gene that correlate with receptor dysfunction, including enhanced platelet activation in deep vein thrombosis and increased intimal hyperplasia ( 19-21 ) and, more recently, with increased occurrence of major obstruction in patients with coronary artery disease ( 19,22,23 ) …”
mentioning
confidence: 99%
“…Prostacyclin also acts as a critical cardio/cytoprotective agent during acute myocardial ischemia ( 15-17 ) and enhances endothelial cell (EC) survival, supporting neovascularization ( 18 ). Several single-nucleotide polymorphisms occur in the hIP gene that correlate with receptor dysfunction, including enhanced platelet activation in deep vein thrombosis and increased intimal hyperplasia ( 19-21 ) and, more recently, with increased occurrence of major obstruction in patients with coronary artery disease ( 19,22,23 ) …”
mentioning
confidence: 99%
“…The exception is performed by the fluorinated series of compounds, whose ethyl ester derivatives seem to be more selective than the bulkier analogues (i-propyl and n-butyl derivatives). Since the hydrolysis of the ester can occur at least to some extent in vivo, ester compounds 26-32 and 59-66 were evaluated in comparison with the corresponding acid (19)(20)(21)(22)(23)(24)(25) [25g]. In general the ester derivatives proved to be more effective and selective toward COX-2 with respect to acid derivatives and only in the case of 3-F phenyl substituted derivatives the acid compound 23 and the esters compounds 30, 61 and 62 displayed closer potencies.…”
Section: Biological and Pharmacological Evaluationmentioning
confidence: 99%
“…reduced generation of the second messenger c-AMP after activation of the receptor [22]. Importantly, Arehart et al [22] have shown that patients who were carriers of the SNP R212C were associated with increased cardiovascular disease and events, analogously to COX-2 inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…We also report one mutation that is associated with a signifi cantly higher incidence in the cardiovascular disease cohort. ( 35 ). Genomic DNA was extracted from blood using a PuregeneH system (Gentra Systems).…”
Section: Measurement Of Intracellular Calcium Concentrationmentioning
confidence: 99%